Membangun Desa di Balai Desa Kadu, Kabupaten Sumedang, Kabupaten Sumedang, Jawa Barat. Pada program Medeka Belajar Kampus Merdeka (MBKM) - Arief Rijaluddin; Wulan Mariliana Muharomah; Muhammad Farras Raihan Ramdhani; Dina Natalia; Raharja Gumilar; Muhammad Wafi Hariry (Universitas Majalengka, 2021)
In the Medeka Belajar Kampus Merdeka (MBKM) Building the Village program, we realised one of the Tri Dharma of higher education, namely the field of service. The purpose of implementing this programme is that students are expected to gain learning experience through direct involvement in the community. find, formulate, solve and overcome problems in the field. As for the target audience of the village development that we carried out, namely designing and designing and making a Budget Plan (RAB) for the infrastructure of the Retaining Wall (DPT) in Kadu Village, Sumedang Regency. The MBKM Membangun Desa model is utilised as an intracurricular activity that combines the implementation of the Tridharma of Higher Education with the method of providing knowledge and work experience to us in planning, implementing, and managing DPT infrastructure. work experience in planning, implementing and supervising village development, by applying the knowledge of village development, by applying the knowledge of the subjects taught as a support for the implementation of MBKM Membangun Desa activities, so that the final report of the activity is submitted as a course assessment. The final report of the activity is submitted as an assessment of the course taught.